When they listen and when they watch: Pianists’ use of nonverbal audio and visual cues during duet performance - Bishop, Laura (Music Sci, 2015)
Nonverbal auditory and visual communication helps ensemble musicians predict each other’s intentions and coordinate their actions. When structural characteristics of the music make predicting co-performers’ intentions diﬃcult (e.g., following long pauses or during ritardandi), reliance on incoming auditory and visual signals may change. This study tested whether attention to visual cues during piano–piano and piano–violin duet performance increases in such situations. Pianists performed the secondo part to three duets, synchronizing with recordings of violinists or pianists playing the primo parts. Secondos’ access to incoming audio and visual signals and to their own auditory feedback was manipulated. Synchronization was most successful when primo audio was available, deteriorating when primo audio was removed and only cues from primo visual signals were available. Visual cues were used eﬀectively following long pauses in the music, however, even in the absence of primo audio. Synchronization was unaﬀected by the removal of secondos’ own auditory feedback. Diﬀerences were observed in how successfully piano–piano and piano–violin duos synchronized, but these eﬀects of instrument pairing were not consistent across pieces. Pianists’ success at synchronizing with violinists and other pianists is likely moderated by piece characteristics and individual diﬀerences in the clarity of cueing gestures used.